1991
DOI: 10.1113/jphysiol.1991.sp018377
|View full text |Cite
|
Sign up to set email alerts
|

Responses of slowly and rapidly adapting receptors in the airways of rabbits to changes in the Starling forces.

Abstract: SUMMARY1. The responses of the rapidly adapting receptors (RARs) and the slowly adapting receptors (SARs) of the airways to changes in the Starling forces regulating fluid exchange in the pulmonary extravascular space were investigated in anaesthetized rabbits. The hydrostatic pressure in the pulmonary microvasculature was raised by partial obstruction of the mitral valve (mean left atrial pressure increased by approximately 5 and 10 mmHg above the control values) and the concentration of plasma proteins was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…However, if subclinical pulmonary edema is of hydrostatic origin, it is likely to occur at much lower Ppas than those seen in clinical HAPE. Hargreaves et al (13) demonstrated increased activity in rabbit airway rapidly adapting receptors suggestive of a physiological effect from interstitial edema after an increase in left atrial pressure of as little as 5 mmHg. In keeping with the findings of Boussuges et al (3), we also found alterations in transmitral flow on echo-Doppler with a decrease in the E/A ratio on ascent to high altitude, suggestive of a reduction in left ventricular diastolic compliance.…”
Section: Discussionmentioning
confidence: 99%
“…However, if subclinical pulmonary edema is of hydrostatic origin, it is likely to occur at much lower Ppas than those seen in clinical HAPE. Hargreaves et al (13) demonstrated increased activity in rabbit airway rapidly adapting receptors suggestive of a physiological effect from interstitial edema after an increase in left atrial pressure of as little as 5 mmHg. In keeping with the findings of Boussuges et al (3), we also found alterations in transmitral flow on echo-Doppler with a decrease in the E/A ratio on ascent to high altitude, suggestive of a reduction in left ventricular diastolic compliance.…”
Section: Discussionmentioning
confidence: 99%
“…According to these observations, pulmonary edema should not be an expected cause of cough, unless fluid accumulation is severe enough to build up within the airways, producing a soft moist cough accompanied by blood‐tinged sputum . Although there is a reported correlation between action potentials generated by coughing receptors and mean left atrial pressure in anesthetized rabbits, a direct association between resulting peribronchial edema and coughing is not reported . Nevertheless, in many veterinary textbooks, cough commonly is associated with the presence of cardiogenic pulmonary edema in dogs .…”
mentioning
confidence: 99%
“…Stimulation of C-fibers in the airways is known to trigger the release of substance P and other tachykinins [19], which can in turn lead to the production of nitric oxide from endothelial cells [34]; nitric oxide, an endogenous free radical gas, can increase the microvascular permeability and fluid infiltration into the perivascular interstitial space in the airways, and activate RARs [35]. Indeed, it has been shown that right atrial injection of lactic acid stimulates a small percentage of RARs in the rat lung [36].…”
Section: Effect Of Acid On Sensory Nerves Innervating the Airways mentioning
confidence: 99%